Sustainable financing, scaling up WASH [Water, Sanitation and Hygiene] and urban agriculture - Veenhuizen, René van; Bruijne, G. de; Otoo, Miriam (2013)
Sustainable financing can be viewed from two perspectives. According to the first, an adequate mix of public and private financing, and significant reliance on local finance options, for any activity is necessary to avoid dependency on external funding (often project related). The second perspective relates to the purpose of the investment, focusing here on value chains in the sanitation and (peri)urban agricultural (UPA) sectors. This issue, no. 26, is a collaborative effort of the RUAF Foundation and WASTE, both members of the Dutch WASH Alliance. The emphasis is on exploring options for the financing of urban agriculture as part of the sanitation value chain: valorisation of urban waste with clear benefit impacts to the urban and periurban agricultural sector.